Adenosine stimulates the basolateral 50 pS K+ channel in renal proximal tubule via adenosine-A1 receptor - Liu, Hao; Sun, Qi; Ding, Zheng; Shi, Wensen; Wang, Wen-Hui; Zhang, Chengbiao (Frontiers in Physiology, 2023)
Background: The basolateral potassium channels play an important role in maintaining the membrane transport in the renal proximal tubules (PT) and adenosine receptors have been shown to regulate the trans-epithelial Na+ absorption in the PT. The aim of the present study is to explore whether adenosine also regulates the basolateral K+ channel of the PT and to determine the adenosine receptor type and the signaling pathway which mediates the effect of adenosine on the K+ channel. Methods: We have used the single channel recording to examine the basolateral K+ channel activity in the proximal tubules of the mouse kidney. All experiments were performed in cell-attached patches. Results: Single channel recording has detected a 50 pS inwardly-rectifying K+ channel with high channel open probability and this 50 pS K+ channel is a predominant type K+ channel in the basolateral membrane of the mouse PT. Adding adenosine increased 50 pS K+ channel activity in cell-attached patches, defined by NPo (a product of channel Numbers and Open Probability). The adenosine-induced stimulation of the 50 pS K+ channel was absent in the PT pretreated with DPCPX, a selective inhibitor of adenosine A1 receptor. In contrast, adenosine was still able to stimulate the 50 pS K+ channel in the PT pretreated with CP-66713, a selective adenosine A2 receptor antagonist. This suggests that the stimulatory effect of adenosine on the 50 pS K+ channel of the PT was mediated by adenosine-A1 receptor. Moreover, the effect of adenosine on the 50 pS K+ channel was blocked in the PT pretreated with U-73122 or Calphostin C, suggesting that adenosine-induced stimulation of the 50 pS K+ channels of the PT was due to the activation of phospholipase C (PLC) and protein kinase C (PKC) pathway. In contrast, the inhibition of phospholipase A2 (PLA2) with AACOCF3 or inhibition of protein kinase A (PKA) with H8 failed to block the adenosine-induced stimulation of the 50 pS K+ channel of the PT. Conclusion: We conclude that adenosine activates the 50 pS K+ channels in the basolateral membrane of PT via adenosine-A1 receptor. Furthermore, the effect of adenosine on the 50 pS K+ channel is mediated by PLC-PKC signaling pathway.